2019
DOI: 10.20961/carakatani.v34i2.30434
|View full text |Cite
|
Sign up to set email alerts
|

GGE-Biplot Analysis for Soybean Varieties Suitability in an Agroforestry System based on Kayu Putih Stands

Abstract: <p>The existence of genotype and environment (G x E) interaction causes difficulty in selecting suitable varieties of soybean in an agroforestry system based on <em>kayu putih</em> stands. This study aimed to determine the suitability of adaptive, stable and high yield soybean varieties in an agroforestry system based on <em>kayu putih</em> stands by using GGE-Biplot analysis. The experiment was conducted from May to August 2018 at Menggoran Forest Resort, Playen District, Gunung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Soybean varieties showed difference in yield per hectare when grown in Lithic Haplusterts, Ustic Epiaquerts and Vertic Haplustalfs. This was due to the G × E interaction so that each soybean varieties response differently to each soil types (Alam et al, 2019). The relationship between productivity and soil was very complex and highly dependent on the physical, chemical and biological nature of the soil and external factors (Adams, 2016;Sys et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean varieties showed difference in yield per hectare when grown in Lithic Haplusterts, Ustic Epiaquerts and Vertic Haplustalfs. This was due to the G × E interaction so that each soybean varieties response differently to each soil types (Alam et al, 2019). The relationship between productivity and soil was very complex and highly dependent on the physical, chemical and biological nature of the soil and external factors (Adams, 2016;Sys et al, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…It can maximize the potential yield of these varieties and reduced fertilizer input (European Union, 2012). Alam et al, (2019) reported that Dering I and Devon I varieties had higher stability as well as higher mean of yield and Burangrang, Grobogan and Gema gave medium-high yield and poor yield with poor adaptation. However, the unknown soil quality parameters are a limiting factor for soybean production.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted from November 2019 to February 2020 in Menggoran Forest Resort, Playen Forest Section, Yogyakarta Forest Management District, Indonesia (Figure 1a). The study site is at an altitude of ±100 meters above sea level and has a ustic moisture regime: annual mean temperature, relative humidity, and precipitation of 29.38 °C, 81.90%, and 1,182 mm year −1 , respectively (Alam et al 2019a;Alam et al 2019b;Alam et al 2021;Suryanto et al 2017;Suryanto et al 2020b). This regime is composed of limited moisture but is suitable for plant growth when environmental conditions are favorable and when the water requirements for plants are met (Boettinger et al 2015).…”
Section: Study Sitementioning
confidence: 99%
“…The mean air temperature (Tair) and the relative humidity (RH) were 29.38°C and 81.90%, respectively. The study site had ustic soil moisture regime (Alam et al 2019a;Alam et al 2019b;Suryanto et al 2017a). Ustic is a soil regime containing limited moisture but is suitable for plant growth when the environmental conditions favorable when the water requirements for plants fulfilled (Boettinger et al 2015).…”
Section: Experimental Areamentioning
confidence: 99%
“…Soil in the study site was classified as Lithic Haplusterts (Alam et al 2019a;Alam et al 2019b;Suryanto et al 2017a). Lithic Haplusterts is a Vertisol soil type that has shallow solum and a lithic contact within 50 cm of the soil surface (Soil Survey Staff 2014).…”
Section: Experimental Areamentioning
confidence: 99%